2021
DOI: 10.3389/fncel.2021.703431
|View full text |Cite
|
Sign up to set email alerts
|

Transmembrane Protein TMEM230, a Target of Glioblastoma Therapy

Abstract: Glioblastomas (GBM) are the most aggressive tumors originating in the brain. Histopathologic features include circuitous, disorganized, and highly permeable blood vessels with intermittent blood flow. These features contribute to the inability to direct therapeutic agents to tumor cells. Known targets for anti-angiogenic therapies provide minimal or no effect in overall survival of 12–15 months following diagnosis. Identification of novel targets therefore remains an important goal for effective treatment of h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
25
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(27 citation statements)
references
References 132 publications
(143 reference statements)
2
25
0
Order By: Relevance
“…The addition of secreted factors generated from glial cells in which TMEM230 expression was upregulated to human umbilical vein endothelial cell (HUVEC) cultures resulted in endothelial cell sprouting and blood-vessel-like structure formation. Collectively, our previous studies have supported that expression of TMEM230 promotes the infiltration of various cell types [5], including microglia, macrophages, endothelial cells, and immune cells.…”
Section: Introductionsupporting
confidence: 62%
See 3 more Smart Citations
“…The addition of secreted factors generated from glial cells in which TMEM230 expression was upregulated to human umbilical vein endothelial cell (HUVEC) cultures resulted in endothelial cell sprouting and blood-vessel-like structure formation. Collectively, our previous studies have supported that expression of TMEM230 promotes the infiltration of various cell types [5], including microglia, macrophages, endothelial cells, and immune cells.…”
Section: Introductionsupporting
confidence: 62%
“…Sustained over-expression of TMEM230 in endothelial cells also promoted loss of normal blood vessel structure and function by inducing loss of cellto-cell contacts [6]. Recently, we demonstrated that TMEM230 induces vascular mimicry by secretion of glial and macrophage cellular proteins and glycan-digesting enzymes and glycoproteins that have microchannel-and scar-forming capacity [5]. The addition of secreted factors generated from glial cells in which TMEM230 expression was upregulated to human umbilical vein endothelial cell (HUVEC) cultures resulted in endothelial cell sprouting and blood-vessel-like structure formation.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…Upregulation of HOTAIRM1 expression in GBM cells promotes cell migration and invasion, suggesting that targeting HOTAIRM1 is also a possible therapeutic strategy for GBM 35 . Elevated transmembrane protein TMEM230 in GBM can promote tumor cell migration, extracellular stent remodeling, and excessive blood vessels and abnormal formation of blood vessels, so TMEM230 has the potential be a therapeutic target for inhibition of GBM tumor cells and anti-angiogenesis 36 . PDRG1 is abnormally highly expressed in GBM, promoting the migration and proliferation of GBM cells through the MEK/ERK/CD44 pathway 37 .…”
Section: Discussionmentioning
confidence: 99%